1995
DOI: 10.1089/neu.1995.12.659
|View full text |Cite
|
Sign up to set email alerts
|

Biomechanics of Skull Fracture

Abstract: This study was conducted to determine the biomechanics of the human head under quasistatic and dynamic loads. Twelve unembalmed intact human cadaver heads were tested to failure using an electrohydraulic testing device. Quasistatic loading was done at a rate of 2.5 mm/s. Impact loading tests were conducted at a rate of 7.1 to 8.0 m/s. Vertex, parietal, temporal, frontal, and occipital regions were selected as the loading sites. Pathological alterations were determined by pretest and posttest radiography, close… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
187
3

Year Published

2003
2003
2018
2018

Publication Types

Select...
4
1
1

Relationship

1
5

Authors

Journals

citations
Cited by 236 publications
(202 citation statements)
references
References 4 publications
12
187
3
Order By: Relevance
“…They are also not excessively high considering that all of these people sustained moderately severe head injury. Forces on the head, similarly, fall within more acceptable levels compared to the literature, and the only case that still exceeds the highest fracture limit found by Yoganandan et al [16] and Allsop et al [17] (Case 3) is one that actually did have skull fracture. With regards to angular acceleration figures for these simulations, they do reduce significantly, but not by the same factor that linear acceleration does.…”
Section: Altering Head Contact Characteristicssupporting
confidence: 52%
See 4 more Smart Citations
“…They are also not excessively high considering that all of these people sustained moderately severe head injury. Forces on the head, similarly, fall within more acceptable levels compared to the literature, and the only case that still exceeds the highest fracture limit found by Yoganandan et al [16] and Allsop et al [17] (Case 3) is one that actually did have skull fracture. With regards to angular acceleration figures for these simulations, they do reduce significantly, but not by the same factor that linear acceleration does.…”
Section: Altering Head Contact Characteristicssupporting
confidence: 52%
“…Thomson et al [25] found angular acceleration values of between 7 and 30 krad/s 2 in reconstructions of severe head injury accidents involving vehicles). Force values for all of these simulations apart from Case 1 also exceed the highest tolerance limits established for skull fracture (14.1 kN [16] or 17.0 kN [17]), with fracture actually only occurring in two cases. In many simulations, these limits are exceeded by a great amount -enough to suggest much more extensive fracture of the skull than the relatively simple linear fractures present in the two cases showing skull fracture.…”
Section: Altering Head Contact Characteristicsmentioning
confidence: 64%
See 3 more Smart Citations